Pembelajaran Organisasi UKM untuk Menciptakan Keunggulan Bersaing - A.S, Fathor; Arief, Mohammad (Jurnal Ekonomi Modernisasi, 2017)
The purpose of article writing is to develop a conceptual framework of organizational learning for SMEs to create competitive advantage. Individual knowledge in organizations is the key to success in organizational learning. The application of organizational learning can be used to develop the organization through the determination of organizational design. Organizations in the learning stages should be directed to the organic organizational design as it encourages individuals to demonstrate innovative behavior, increased efficiency, effective and appropriate change applied to uncertain environments. This can create competitive advantage for SMEs.